Structure of ADC‐68, a novel carbapenem‐hydrolyzing class C extended‐spectrum β‐lactamase isolated from Acinetobacter baumannii. (1st November 2014) - Jeon, Jeong Ho; Hong, Myoung‐Ki; Lee, Jung Hun; Lee, Jae Jin; Park, Kwang Seung; Karim, Asad Mustafa; Jo, Jeong Yeon; Kim, Ji Hwan; Ko, Kwan Soo; Kang, Lin‐Woo; Lee, Sang Hee
<x xml:space="preserve">Abstract</x> Outbreaks of multidrug‐resistant bacterial infections have become more frequent worldwide owing to the emergence of several different classes of β‐lactamases. In this study, the molecular, biochemical and structural characteristics of an Acinetobacter‐derived cephalosporinase (ADC)‐type class C β‐lactamase, ADC‐68, isolated from the carbapenem‐resistant A. baumannii D015 were investigated. The blaADC‐68 gene which encodes ADC‐68 was confirmed to exist on the chromosome via Southern blot analysis and draft genome sequencing. The catalytic kinetics of β‐lactams and their MICs (minimum inhibitory concentrations) for A. baumannii D015 and purified ADC‐68 (a carbapenemase obtained from this strain) were assessed: the strain was resistant to penicillins, narrow‐spectrum and extended‐spectrum cephalosporins, and carbapenems, which were hydrolyzed by ADC‐68. The crystal structure of ADC‐68 was determined at a resolution of 1.8 Å. The structure of ADC‐68 was compared with that of ADC‐1 (a non‐carbapenemase); differences were found in the central part of the Ω‐loop and the C‐loop constituting the edge of the R1 and R2 subsites and are close to the catalytic serine residue Ser66. The ADC‐68 C‐loop was stabilized in the open conformation of the upper R2 subsite and could better accommodate carbapenems with larger R2 side chains. Furthermore, a wide‐open conformation of the R2‐loop allowed ADC‐68 to bind to and hydrolyze extended‐spectrum cephalosporins. Therefore, ADC‐68 had enhanced catalytic efficiency against these clinically important β‐lactams (extended‐spectrum cephalosporins and carbapenems). ADC‐68 is the first reported enzyme among the chromosomal class C β‐lactamases to possess class C extended‐spectrum β‐lactamase and carbapenemase activities.